Polynomial invariants of G-orbit errors of BCH codes and its application - V. A. Lipnitski; E. V. Sereda (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The article addresses the further development of methods of BCH codes norm decoding. The authors propose to use new syndrome invariants - polynomial invariants of automorphism group G of a family of BCH codes. The paper presents basic properties of polynomial invariants and errors correction technique considered on two-step iteration system of error identification. An efficiency of the method of decoding based on polynomial invariants of G -orbit is demonstrated by the example.